Phase-field modeling of an abrupt disappearance of solute drag in rapid solidification. (15th May 2015) - Wang, Haifeng; Galenko, P.K.; Zhang, Xiao; Kuang, Wangwang; Liu, Feng; Herlach, D.M.
Abstract: An effective mobility for non-equilibrium solute diffusion is introduced to develop a hyperbolic phase-field model of rapid solidification in which long-range solute diffusion and short-range solute-redistribution are under local non-equilibrium conditions. At equilibrium, the model provides decoupling of bulk and interface properties. Far from equilibrium, the model predicts a transition from diffusion-limited growth to diffusionless solidification at an interface velocity that is equal to the solute diffusion speed in liquid. At this critical velocity, the solute drag effect disappears abruptly, being consistent with the previous local non-equilibrium model for the sharp interface. A comparison with other phase-field models is made and an agreement between the present model predictions and the experimental results of rapid solidification of Si-9at.%As alloy is obtained.